The Impact of Bankruptcy on Airline Service Levels - Borenstein, Severin; Rose, Nancy L (American Economic Review, 2003)
The current financial crisis in the commercial airline industry has engendered an active debate over appropriate governmental policies. Proponents of government support, instrumental in legislating a $5 billion cash transfer and $10 billion loan guarantee fund for U.S. carriers following September 11, 2001, point to the critical role that airlines play in the U.S. economy and the devastating effects airline failures could have on air service. Opponents argue that most airlines continue to operate through bankruptcy resolution and that even a complete shutdown of a major carrier, which rarely occurs, would stimulate expansion by other airlines to replace its abandoned flights. This debate highlights the need to understand the causal effect of airline financial distress on airline operations, distinct from correlations that may exist as a result of adverse demand or cost shocks that lead to both service declines and financial distress. We focus on airline Chapter 11 bankruptcy filings, an extreme measure of financial distress. We use data from 1984 through 2001 to evaluate the impact of major bankruptcies on the level of flights and destinations served at U.S. airports. Our results suggest that bankruptcy induces modest declines in service levels, particularly at midsize airports. This raises the question of whether such declines are socially inefficient. Restrictions imposed by the bankruptcy court judge or the creditors of an airline operating under Chapter 11 may affect total industry output or capacity offered if other carriers cannot rapidly replace the production of the constrained firm (i.e., if firms are not homogeneous and entry is not costless). With heterogeneous firms, one firm may be uniquely positioned to supply a flight, and its decision not to do so may lead to a reduction in total service. This is particularly likely in network industries, such as airlines, where there are strong production complementarities across routes. It is also possible, however, that pre-bankruptcy service levels were inefficiently high. The bankrupt carrier may have overprovided service, perhaps in an attempt to build market share, or flight-frequency competition among carriers may have led to excessive flights. In these cases, the flight reduction associated with bankruptcy may cause a movement toward the socially optimal level of service. Our work takes a first step toward resolving this issue, by determining the magnitude of bankruptcy effects on aggregate air service. The results suggest the need for further research to assess its possible welfare implications.